116 PROGNOSTIC IMPACT OF THE SHORT-AXIS DIAMETER FOR THE NODAL ASSESSMENT BEFORE PREOPERATIVE CHEMOTHERAPY IN ESOPHAGEAL CANCER. (17th September 2021) - Ichikawa, Hiroshi; Sudo, Natsuru; Bamba, Takeo; Hanyu, Takaaki; Kano, Yosuke; Motegi, Daisuke; Muneoka, Yusuke; Ishikawa, Takashi; Hirose, Yuki; Miura, Kohei; Takizawa, Kazuyasu; Nakano, Masato; et al.
Abstract: : Clinical N category (cN) is generally assessed by measuring the nodal diameter by CT before the initiation of primary treatment in esophageal squamous cell carcinoma (ESCC). The short-axis diameter is recommended for evaluating treatment response in solid tumors by RECIST. This study aimed to elucidate the prognostic implication of the maximum short-axis diameter of lymph node (cN-size) before preoperative chemotherapy for ESCC. Methods: We enrolled a total of 152 patients who underwent preoperative cisplatin/5-fluorouracil therapy (CF) followed by esophagectomy from 2005 to 2011. There were 127 men and 25 women with a median age of 65 years (range: 47–79 years). Clinically metastatic node was defined as follows; the node with cN-size ≥10 mm or that with 5 mm ≤ cN-size <10 mm and contrast enhancement, round shape and/or central necrosis in CT before starting CF. The association between the maximum cN-size and the overall survival (OS) after surgery was statistically investigated. The median follow-up period was 87 months (range: 36–145 months). Results: The number of patients with cN0 and cN1–3 was 60 and 92, respectively. Twenty-seven and 65 patients with cN1–3 were classified into cN-size <10 mm and cN-size ≥10 mm group, respectively. The 5-year OS rates in cN0, cN-size <10 mm and cN-size ≥10 mm groups were 70%, 51% and 45%, respectively (P = 0.006). Among Ut-Mt tumors, the OS in the cN-size <10 mm group was significantly worse than that in the cN0 group (5-year OS rate: 45% vs. 74%, P = 0.048). However, there were no significant differences in the OS between these two groups in Lt tumors (67% vs. 64%, P = 0.789). Conclusion: The maximum short-axis diameter of lymph node before preoperative chemotherapy is significantly associated with OS in patients with ESCC. Lymph node with 5 mm ≤ cN-size <10 mm in the short axis should be treated as a metastatic node especially in Ut or Mt tumors, considering the poor prognosis.